AI-Driven Solutions for IT Resource Management - Annam, Srinikhil (International Journal of Engineering and Management Research, 2024)
Effective resource management plays a vital role in such an efficient, cost-effective, and scalable infrastructure when most organizations depend on IT infrastructure. Classical approaches often break down in complex modern environments of IT. Artificial intelligence presents transformative abilities in the management of resources in IT by applying predictive analytics, automation, and optimization. This paper addresses the integrating theme of AI in IT resource management from methodologies to applications, technological frameworks, to ethical considerations. Deeper insight is provided to the AI-driven tools in resource allocation, predictive capability planning, and cost optimization on metrics and technical data. Challenges in privacy, scalability, and fairness are discussed, and future innovations comprise edge computing and self- governing IT systems.